Nossos ossos : a violência em Marcelino Freire - Teles, Euler Lopes (2017)
The aim of this paper consists in analyzing the violence in Marcelino Freire’s work, Nossos sonhos (2013). First, we will discuss the recurrence of violence in our society, trying to understand how from the modernity it seems to have trivialized itself and how it influences the literary production nowadays. It will be used as theoretical contribution about modernity Berman (2007), Bauman (1998; 2001) and Giddens’ (1991) texts and about the evil Ricouer (1988) and Rosenfield (2003); after that, we will analyze how this theme has fomented Marcelino Freire’s writing studying Souza (2012), Vasconcelos (2007), Rocha (2015) e Santana (2015); then, we will discuss the evil in the cities and how in the work, from the narrator's memories, we contrast the great city and sertão of Pernambuco, and we will also try to identify the relation between Nossos ossos and the literature in the 30’s, for that we will use Albuquerque Jr (2001), Halbswachs (2006), Candido (1989) and Bueno’s (2006) texts; still about the fragmented contemporary narrator, we will approach Benjamin (1994), Santiago (1989) and Hall (2001). Later, we will discuss the relation between body and crime, pointing the relation between body of romance and the elements of the police narrative, supported in Mandel (1993) and Todrov (1979), in a parody perspective reading Hutcheon (1989) and Samoyault (2008); next, we will go deeper in the discussion between body, crime and literature by reading Ludmer (2002), Agamben (2002) and Bergson (2006), and in the sequence between characters that represent cyborgs people, defining the relation between body and machine, using Haraway (2009), Doel (2001), Kunzuru (2001) and Santaela (2003). And, finally, it will be discussed the matters related to double and otherness and how they are imbricated for the understanding of the spreading of the evil resorting Bravo (2005), Rosset (1988) and Kalina and Koyadloff’s (1989) texts; we will also trace a relation between the work and the theater from Motta (2011), Rosenfeld (2014), Artaud’s (1993) texts; and then, especially, with a performance by means of Calson (2011), Puchner (2013), Ramos (2013) and Fernandes’ (2009) texts.